Suicide causes, motives, methods of prevention and treatment - Zaatrh, Inaam Eid Mohammad; Alhallaq, Iyad Selim AbdulRazzaq (Arab Journal for Sciences and Research Publishing, 2024)
The phenomenon of suicide is a sensitive issue that requires a deep understanding of the motives and causes behind this tragic human behavior. Dealing with this issue comprehensively is necessary to provide a balanced view that allows us to understand and prevent it. In this article, we will review a range of motives and factors that may lead individuals to make desperate decisions. Psychological motives include depression and mental disorders, which are among the most crucial psychological motives for suicide. In addition to anxiety and psychological pressures where some individuals live in environments full of psychological pressures and anxiety, which negatively affect their mental health and make them vulnerable to suicide as a means to escape from these pressures. Social factors include social isolation, which is considered a significant influencing factor, as the individual lacks the necessary social support that can be a vital factor in facing the challenges. Cultural factors include traditions and social expectations, which play a significant role in shaping individuals' self-image, and some may feel despair if they cannot achieve these expectations. Additionally, some cultures face additional challenges in talking about mental health, leading to neglect of mental issues and the exacerbation of problems.
Keywords: Suicide; Suicidal Ideation; Suicide Attempt